LncRNAs and Chromatin Modifications Pattern m6A Methylation at the Untranslated Regions of mRNAs - Vaasjo, Lee O. (Frontiers in Genetics, 2022)
New roles for RNA in mediating gene expression are being discovered at an alarming rate. A broad array of pathways control patterning of N6-methyladenosine (m6A) methylation on RNA transcripts. This review comprehensively discusses long non-coding RNAs (lncRNAs) as an additional dynamic regulator of m6A methylation, with a focus on the 5’UTR. Although there is extensive literature describing m6A modification of lncRNA, the function of lncRNA in guiding m6A Writers have not been thoroughly explored. The independent control of lncRNA expression, its heterogeneous roles in RNA metabolism, and its interactions with epigenetic machinery, alludes to their potential in dynamic patterning of m6A methylation. While epigenetic regulation by histone modification of H3K36me3 has been demonstrated to pattern RNA m6A methylation, these modifications were specific to the coding and 3’UTR regions. However, there are observations that 5’UTR m6A is distinct from that of the coding and 3’UTR regions, and substantial evidence supports the active regulation of 5’UTR m6A methylation. Consequently, two potential mechanisms in patterning 5’UTR m6A methylation are discussed; (1) Anti-sense lncRNA (AS-lncRNA) can either bind directly to the 5’UTR, or (2) act indirectly via recruitment of chromatin-modifying complexes to pattern m6A. Both pathways can guide the m6A Writer complex, facilitate m6A methylation and modulate protein translation. Findings in the lncRNA-histone-m6A axis could potentially contribute to the discovery of new functions of lncRNAs and clarify lncRNA-m6A findings in translational medicine.